Hate speech and LGBT media framing effects among community - Mohd Zawawi, Julia Wirza; Hasan, Hamisah (Human Resource Management Academic Research Society, 2021)
The development of communication technology facilitates the users to get fast and easy information. Furthermore, with this platform all users will create and upload news content, and interested readers can get it through social media. The attainability can be seen to have either negative or positive possibilities. This study conducted took the example of Lesbian, Gay, Bisexual and Transgender (LGBT) issue as the core on how negative media content display gives different effect whether to the change of attitude and behaviour of an individual. Using experimental study approach, this study will have some main objectives namely to see the hate speech display effect related to LGBT on individual. Second, compares positive or negative message or news display on change of attitude and behaviour of an individual. The analysis using descriptive analysis and Paired Sample T-Test and Analysis of Variants (ANOVA) will idenfity how far the hate speech message display effect on an individual. The findings show that positive frame gives effect compared to the negative frame on readers’ attitude and behaviour. Besides that, significant change towards the change of attitude compared to the change of behaviour.